PEMANFAATAN LIMBAH STYROFOAM SEBAGAI CAMPURAN PEMBUATAN BATA RINGAN - Oemiati, Nurnilam; Jonizar, Jonizar; Tri Meyrian, Aang (Universitas Muhammadiyah Palembang, 2022)
Lightweight bricks are bricks that have a specific gravity lighter than bricks in general. Lightweight bricks can also be made using additives, such as alumina powder which produces gas when the concrete is still plastic or by using aggregates of low density, such as pumice, volcanic ash, and diatomite rock, which are the most commonly used natural aggregates. Styrofoam is inseparable from efforts in utilizing waste to be taken from around the Palembang area. Thus the addition of styrofoam waste will not have a negative impact on the environment because it can be used as lightweight bricks. (0%) 241 kg/cm2, styrofoam mix (20%) 82.3 kg/cm2, styrofoam mix (40%) 75.25 kg/cm2, styrofoam mix (60%) 26.4 kg/cm2 , styrofoam mix (80%) 9.05 kg/cm2, styrofoam mixture (100%) 0 kg/cm2.